Preclinical findings: The pharmacological targets and molecular mechanisms of ferulic acid treatment for COVID-19 and osteosarcoma via targeting autophagy - Pang, Guangfu; Yi, Tingzhuang; Luo, Hongcheng; Jiang, Lihe (Frontiers in Endocrinology, 2022)
The variant virus-based 2019 coronavirus disease (COVID-19) pandemic has reportedly impacted almost all populations globally, characterized by a huge number of infected individuals. Clinical evidence proves that patients with cancer are more easily infected with severe acute respiratory disease coronavirus 2 (SARS-CoV-2) because of immunologic deficiency. Thus, there is an urgent need to develop candidate medications to treat patients with cancer plus COVID-19, including those with osteosarcoma (OS). Ferulic acid, a latent theriacal compound, is discovered to have potential pharmacological use, including having anti-tumor and anti-virus activities. Thus, in this study, we aimed to screen and determine the potential therapeutic targets of ferulic acid in treating patients with OS plus COVID-19, as well as the pharmacological mechanisms. We applied a well-established integrated methodology, including network pharmacology and the molecular docking technique to detail target prediction, network construction, gene ontology, and pathway enrichment in core targets. The network pharmacology results show that all candidate genes, by targeting autophagy, were the core targets of ferulic acid in treating OS and COVID-19. Through the molecular docking analysis, signal transducer and activator of transcription 3 (STAT3), mitogen-activated protein kinase 1 (MAPK1), and phosphoinositide-3-kinase regulatory subunit 1 (PIK3R1) were identified as the pharmacological targets of ferulic acid in treating OS. Altogether, these preclinical findings from bioinformatics analysis effectively determined the pharmacological molecules and mechanisms via targeting autophagy that exert the therapeutic effectiveness of ferulic acid against COVID-19 and OS.